Herbal Treatment Expert System For Ent Disease Diagnosis Using The Certainty Factor Method Based On Android - Ade Johar Maturidi; Muhammad Ali Fajri; Deni Nurgaha (Jurnal Improsci, 2025)
Background. Public understanding of ENT (ear, nose, and throat) diseases remains low. Many people still rely on experts manually, resulting in high costs for the general public. Aims. This research was conducted to develop a tool to assist users in diagnosing ENT (ear, nose, and throat) diseases in humans. This tool, an expert system, is designed to diagnose and provide herbal treatment recommendations. Result. This expert system application produces an application program or tool that can be used to diagnose possible ENT diseases in humans based on user-entered symptoms. Conclusion. System testing demonstrated that the system can diagnose ENT diseases based on patient symptoms, despite the uncertainty of those symptoms. Implementation. The diagnostic results are accompanied by a Certainty Factor value, which indicates the level of accuracy and predictability of the possible ENT disease in humans, along with the corresponding herbal treatment.